MODELING THE DISTRIBUTION AND USE OF PROFITS IN VARIOUS BUSINESS DEVELOPMENT STRATEGIES - H. V. Sotnikova (Publishing House of the State University of Management, 2019)
The model of distribution and use of profit has been offered. The model provides for the choice of development strategy based on the calculation of the integral indicator of economic potential in terms of financial, economic, market and labor potential of the organization. The criteria are indicative intervals of the integrated indicator of economic potential for each development strategy: anti-crisis, strategy of stable development and strategy of accelerated development. The options for determining the proportions of distribution of net profit in accordance with the adopted strategy and for controlling profit have been considered, providing information to the integrated accounting of the deviation of the actual level of net profit from indicative and allowing you to make corrective solutions: transition to other strategy development or adjustment of the flexible areas of use of profits. The modeling process has been reviewed on the example of a trade organization.